Media by Minority: Bonding and Bridging Strategies of Shia and Ahmadiyya Communities in Indonesia - Iim Halimatusa'diyah; Jamhari Makruf (Al-Jami'ah: Journal of Islamic Studies, 2025)
Representations of minority groups are often examined through mainstream media perspectives, while less attention has been given to how minorities construct and negotiate their own identities through self-representation in media spaces. This article explores how the development of new media has enabled greater participation and representation among minority groups, with a particular focus on the Shia and Ahmadiyya communities in Indonesia. It analyzes how these religious minorities develop and utilize various forms of self-directed communication, referred to as “media by minorities”, and examines the broader social functions of such media practices. Using Robert Putnam’s theory of social capital as an analytical framework, this study draws on in-depth interviews with key informants from both communities. The findings indicate that increasing openness facilitated by the digital media environment has encouraged minority groups to establish diverse media platforms as instruments of self-representation and community engagement. These media initiatives serve two primary functions. First, they act as a bridging mechanism that facilitates communication, understanding, and interaction between minority communities and the wider society, particularly majority groups. Second, they function as a bonding mechanism that strengthens solidarity, collective identity, and internal relationships within the communities. However, despite this increased openness, digital media environments have not fully eliminated negative narratives toward minority groups.[Representasi kelompok minoritas sering kali dikaji dari sudut pandang media arus utama, sementara perhatian terhadap bagaimana kelompok minoritas membangun dan menegosiasikan identitas mereka sendiri melalui praktik representasi diri di ruang media masih relatif terbatas. Artikel ini mengkaji bagaimana perkembangan ‘media baru’ telah memungkinkan partisipasi dan representasi yang lebih luas bagi kelompok minoritas, dengan fokus pada komunitas Syiah dan Ahmadiyah di Indonesia. Studi ini menganalisis bagaimana kedua komunitas agama minoritas tersebut mengembangkan dan memanfaatkan berbagai bentuk komunikasi mandiri yang disebut sebagai “media oleh minoritas”, serta mengeksplorasi fungsi sosial yang lebih luas dari praktik media tersebut. Dengan menggunakan teori modal sosial Robert Putnam sebagai kerangka analisis, penelitian ini melakukan wawancara mendalam dengan informan kunci dari kedua komunitas. Temuan menunjukkan bahwa meningkatnya keterbukaan yang difasilitasi oleh lingkungan media digital telah mendorong kelompok minoritas untuk membangun berbagai platform media sebagai sarana representasi diri dan keterlibatan komunitas. Inisiatif media tersebut memiliki dua fungsi utama. Pertama, berperan sebagai mekanisme penghubung (bridging mechanism) yang memfasilitasi komunikasi, pemahaman, dan interaksi antara komunitas minoritas dan masyarakat luas, khususnya kelompok mayoritas. Kedua, berfungsi sebagai mekanisme pengikat (bonding mechanism) yang memperkuat solidaritas, identitas kolektif, dan relasi internal di dalam komunitas. Meski demikian, keterbukaan ruang media digital belum sepenuhnya menghapus narasi-narasi negatif terhadap kelompok minoritas.]